Health, food security and livelihood diversification in rural Odisha: A review - Rout, D S; Deb, A; Bhadra, P; Nandy, A (Plant Science Today, 2025)
Shifting the livelihood is a genuine reason for maintaining family and grasping opportunity for the sake of development. In rural areas, the cause is intended for the ambition/hope of getting good remuneration which helps to revive the condition of health as well as diet. Due to the livelihood of rural people being mainly agriculture, the diversification of farmers from farming to other livelihoods warns us to be cautious and take necessary steps towards sustainability. This review study was meant to find out the reasons and challenges behind livelihood diversification and its impact on health and food security through a thorough observation of earlier research. After encountering the findings, the positive impacts of the OFFDI and Odisha Reform Programme are appreciated and those plans of work could be suggested to the developmental sectors whether there is a requirement for policy modification and close supervision of the administration of PDS. Nutritional status, health condition, as well as accessibility to medical facilities, are yet far behind the national average and seek more focus. Joint initiatives by the public and government, are suggested for fruitful inclusion of schemes along with health and food security. The goal of promoting climate-smart agriculture is to help primitive people become self-sufficient in terms of food security by producing food grains under difficult agroclimatic conditions at high altitudes. More no. of projects having development aspects can be proposed by NGOs which in turn will help in the reduction of diversification of livelihoods.